Emergency presentation prior to lung cancer diagnosis: A national-level examination of disparities and survival outcomes. (May 2023) - Gurney, Jason; Davies, Anna; Stanley, James; Signal, Virginia; Costello, Shaun; Dawkins, Paul; Henare, Kimiora; Jackson, Chris; Lawrenson, Ross; Whitehead, Jesse; Koea, Jonathan
Highlights: Half of all lung cancers in NZ are preceded by an emergency hospitalisation. This rate is highest for Pacific (62%) and Indigenous Māori (54%) with lung cancer. Pacific have 50% and Māori 21% higher adjusted odds of emergency hospitalisation. Survival is substantially worse when diagnosed following emergency hospitalisation. Abstract: Objectives: A recent multinational investigation of emergency presentation within 30 days of cancer diagnosis, conducted within the International Cancer Benchmarking Programme (ICBP), observed that New Zealand had the highest rate of emergency presentation prior to lung cancer diagnosis compared to other similar countries. Here we use national-level health data to further investigate these trends, focussing on ethnic disparities in emergency presentation prior to lung cancer diagnosis. We have also compared survival outcomes between those who had an emergency presentation in the preceding 30 days to those who did not. Materials and methods: Our study included all lung cancer registrations between 2007 and 2019 on the New Zealand Cancer Registry (N = 27, 869), linked to national hospitalisation and primary healthcare data. We used descriptive (crude and age-standardised proportions) and logistic regression (crude and adjusted odds ratios) analyses to examine primary care access prior to cancer diagnosis, emergency hospitalisation up to and including 30 days prior to diagnosis, and one-year mortality post-diagnosis, both for the total population and between ethnicities. Regression models adjusted for age, sex, deprivation, rurality, comorbidity, tumour type and stage. Results: We found stark disparities by ethnic group, with 62% of Pacific peoples and 54% of Māori having an emergency presentation within 30 days prior to diagnosis, compared to 47% of Europeans. These disparities remained after adjusting for multiple covariates including comorbidity and deprivation (adj. OR: Māori 1.21, 95% CI 1.13–1.30; Pacific 1.50, 95% CI 1.31–1.71). Emergency presentation was associated with substantially poorer survival outcomes across ethnic groups (e.g. 1-year mortality for Māori: no emergency presentation 50%, emergency presentation 79%; adj. OR 2.40, 95% CI 2.10–2.74). Conclusions: These observations reinforce the need for improvements in the early detection of lung cancer, particularly for Māori and Pacific populations, with a view to preventing diagnosis of these cancers in an emergency setting.